Evaluation of Tourism Facilities Management in Tengger Traditional Cultural Tourism Package: A Case Study at Sedaeng Village, Pasuruan Regency - Dewi, Ika Maha; Yogatama, Ahmad Nizar; Anjaningrum, Widiya Dewi (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This community service activity evaluated tourism facility management challenges in the Tengger Traditional Cultural Tourism Package at Sedaeng Village, Pasuruan Regency, addressing operational inefficiencies in ceremonial equipment maintenance, sanitation facilities, and wayfinding systems that compromised visitor experience and community economic benefits. Method: Employing participatory action research over three months (March-June 2025), the study conducted facility audits using Indonesian Tourism Standards, facilitated collaborative workshops with local managers, implemented practical improvements, and evaluated outcomes using mixed methods including before-and-after performance metrics and visitor feedback forms. Practical Applications: Implemented solutions included a simplified digital inventory system, standardized storage protocols for ceremonial equipment (gelang lawe, satak bolong), sanitation renovations, and locally-sourced signage, resulting in 66.7% reduced equipment retrieval time, 40.6% lower damage rates, and 17% higher visitor satisfaction. Conclusion: The study demonstrates that culturally-sensitive facility management interventions significantly enhance operational efficiency in community-based cultural tourism while preserving authenticity, providing a replicable model for similar indigenous tourism destinations seeking sustainable development through academic-community partnerships.